A Study on The Development of Priority Tourism Destinations in The Bromo Tengger, Semeru Area - Anhar , Adrizal Iqbal; Darmawan , M. Muhlis; Rusdi , Raflis; Arifin, Jauhary (The Journal of Management, Digital Business, and Entrepreneurship, 2023)
One indicator of success in tourism development is the importance of considering the technical aspects of planning, namely the existence of a study of tourism potential that will be developed as a tourist area more professionally. This study refers to the GSTC criteria in Bromo Tengger Semeru National Park by analyzing internal and external factors with SWOT analysis, then formulating priorities from alternative strategies through the Analytic Hierarchy Process method. Determining the informants used purposive, snowball, and quota sampling techniques. Data were gathered through observation, interviews, and focus group discussions. Based on the study’s results, implementing sustainable tourism according to the GSTC in Bromo Tengger Semeru National Park has met the criteria but has not been maximized. Based on the study’s results, the implementation of sustainable tourism referring to the GSTC in Bromo Tengger Semeru National Park has met the criteria but has not been maximized because the community does not understand its potential. The SWOT analysis resulted in the weighting of IFAS and EFAS covering S-O (3.81), W-O (3.11), W-T (2.90), and S-T (2.28). S-O obtained the highest weight so that it was continued into the AHP. The order of priority of the alternative S-O strategy based on the AHP method obtained the following results: Developing attractions (33%), strengthening institutions (25%), making event calendars (15%), conservation (11%), infrastructure development (8%), optimizing supporting facilities (5%) and developing agro-tourism (3%)